Multimodal assessment of circadian sleep health in predicting mental health outcomes in adolescents - Duraccio, Kara McRae; Kamhout, Sarah; Wright, Isabella D.; Rugh, Kathleen Erekson; Miskin, Jack; Amdal, McKenna (Frontiers in Sleep, 2023)
Introduction. Aspects of circadian sleep health including circadian alignment, circadian phase, or chronotype may be related to mental health outcomes in adolescents. Using novel and robust data collection methods, this study explored the relationship between adolescents' circadian sleep health and traits related to depression, anxiety, stress, and emotional regulation.Methods. Fifty-two healthy 14-18-year-olds (58% female; 94% European American) participated in this study. Across a 10-day period, participants completed wrist-worn actigraphy. Next, participants completed a dim-light melatonin onset (DLMO) protocol where 12 saliva samples were collected over a 6-hour period to measure circadian phase. Circadian phase was calculated as the duration of time between DMLO to average sleep onset time across the monitoring period. Social jetlag was measured as the discrepancy between sleep times from weekday to weekend. Participants completed the Depression Anxiety Stress Scales (DASS-21), Emotion Regulation Questionnaire (ERQ), and the Morningness-Eveningness Questionnaire for Adolescents (MEQ). Following dichotomizing sleep outcomes into clinically relevant groups (late vs early circadian phase, aligned vs misaligned circadian rhythms, minimal social jetlag vs presence of social jetlag, intermediate to morningness vs eveningness chronotype), we conducted general linear models to determine circadian group differences in mental health outcomes (depression, anxiety, stress, expressive suppression, and cognitive reappraisal) while controlling for gender and pubertal development.Results. Circadian phase had a large effect on depression symptoms in adolescents, with adolescents with later DLMO having significantly higher depression scores than those with earlier DLMO (p = 0.031). Chronotype had a medium but non-significant effect on anxiety and stress symptoms in adolescents, with adolescents with eveningness-tendencies having higher anxiety and stress symptoms than those with intermediate to morningness-tendencies (p's = 0.140 & 0.111, respectively).In the first ever study using gold-standard methodologies to examine the relationship between mental health and circadian sleep health in healthy adolescents, we observed that adolescents with later circadian phase had increased depressive symptoms compared to earlier circadian phase. Furthermore, adolescents who endorsed behaviors that suggest eveningness tendencies may have heightened stress/anxiety. These conclusions encourage future experimental research regarding this topic and may help inform interventions aimed to decrease depression, anxiety, and stress in adolescents.